Levothyroxine supplementation after hemithyroidectomy in patients with low-risk differentiated thyroid cancer: risk factors and withdrawal strategy - Lee, Jin Seok; Ha, Eun Ju; Jeong, Ho Jung; Kim, Soo Young; Kim, Hyeung Kyoo (Frontiers in Endocrinology, 2025)
BackgroundThe American Thyroid Association guidelines recommend maintaining thyroid-stimulating hormone (TSH) levels < 2 mIU/L postoperatively in low-risk patients. Patients with low-risk differentiated thyroid cancer, defined as intrathyroidal tumors without vascular invasion, aggressive histology, or metastasis according to ATA criteria, were included. Many patients who undergo hemithyroidectomy often maintain normal TSH levels, i.e., a euthyroid status, without taking levothyroxine after surgery. However, some patients continue to receive levothyroxine supplementation post-surgery. In this study, we analyzed the risk factors and predictors of levothyroxine withdrawal.MethodsThe medical records of 132 patients who underwent hemithyroidectomy for thyroid cancer at Ajou University Hospital between February 2016 and February 2018 were reviewed. The medical records included data on demographics, type of operation, pathological findings, pre- and postoperative changes in TSH levels, levothyroxine dosage and discontinuation timing, and pre- to postoperative changes in thyroid gland volume. All patients were started on a fixed dose of levothyroxine immediately after surgery, which was subsequently tapered and withdrawn based on the TSH levels.ResultsAmong 132 patients who underwent hemithyroidectomy, 67 (51%) eventually withdrew from postoperative levothyroxine. Of the many dependent variables, multivariate analysis revealed the statistical significance of preoperative TSH levels (P=0.014), preoperative thyroid volume measured by 3-dimensional (3D) CT, and the ratio of preoperative-to-postoperative residual thyroid volume (P=0.026 and P=0.012, respectively). In the subgroup analysis of the group that resumed levothyroxine administration after levothyroxine withdrawal, only the ratio of the preoperative to postoperative residual thyroid volume was statistically significant (P<0.043).ConclusionPreoperative TSH level and thyroid volume were the most important predictors of successful postoperative levothyroxine withdrawal. The pre- to postoperative thyroid volume ratio may be affected by surgery and a ratio of <33% was significantly correlated with the ability to discontinue levothyroxine.